Think before you act: organizing structures of action in technology-induced change. Issue 4 (13th July 2015) - Professor David Pick, Professor Stephen T.T. Teo, Associate Professor Lars Tummers and Professor Cameron Newton, Associate; Yeo, Roland K.; Marquardt, Michael
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore the influence of technology on organizational change during an electronic government implementation in a public organization in East Malaysia. It also examines the interpretation and enactment of technology as affecting organizational performance. Design/methodology/approach – The research utilized a case study approach involving semi-structured interviewing with 18 employees representing department heads, middle managers, and technical officers. The data were triangulated by unobtrusive observations of meetings and work processes as well as archival records. Findings – Technology could either constrain or enable change based on the interplay of intended and unintended use. The way actors interpret the role of technology during change also affects their enactment of technology, leading to both innovation and disruption in work practices. In turn, their enactment patterns shape organizational structure, strategy, and performance. Research limitations/implications – The paper contributes to the organizational change literature by exploring how individual-level change has led to organizational outcomes as a result of technology. It extends the technology enactment and sociomateriality literature by considering technology use as an organizing process to facilitate change in order to understand the interplay of the social and material aspect of technology. Practical implications – Employees should be made aware of and accountable for the consequences of unintended use or avoidance of technology in order to enable positive change. Collective sensemaking of technology-induced change should be encouraged to transform work practices so as to shape organizational structure, strategy, and performance. Originality/value – Unlike similar research, this study extends the structuration perspective of technology in work organizations by exploring how technology enables and constrains organizational change through intended and unintended use. It further illuminates the power of human agency to innovate and organize structures of action that modify social relations and organizational strategy influencing organizational performance.